O clítico "se" com valor reflexo ou recíproco: uma abordagem sociolingüística - Melo, Neide da Silva Souza (2005)
This paper investigates the usage of the clitic "if" with reflecting value or reciprocal in Brazilian Portuguese (BP) and European Portuguese (EP), the aim is to verify the presence and the absence of this reflexive form, in spoken language, in both Portuguese varieties, bearing in mind factors which would be either carrying out the variable or not. It s based in the theory of labovian Sociolinguistics and Parametric Sociolinguistics, this proposal was developed by Tarallo and Kato (1989), which the aim is to explain the change considering the inter and intra-linguistic differences. The corpora used to develop this research consisted of spoken interviews from BP and EP. The corpus of Brazilian Portuguese was carried out by spoken recordings of 45 informers from the city of Uberlândia. The information of the European Portuguese corpus were extracted from interviews of the data base of Fundamental Portuguese Project. Some hypotheses were confirmed by statistics results, others were refused. The analysis showed that between EP and BP there are important differences in regards to spoken language: in BP there is a preference by the deletion of the reflexive clitic "if" the third person, while in EP, the preference by the usage of the pronoun, in question, is noticeable bigger.